Plant conservation in National Parks: vegetation checklist, biogeography and protected habitats (Sierra de las Nieves, Malaga, Spain). - Pérez-Latorre, Andrés Vicente; Casimiro-Soriguer Solanas, Federico; Hidalgo-Triana, Noelia; Cabezudo-Artero, Baltasar (My University, 2024)
A study of the plant communities that develop in the state protected natural area “Parque Nacional de la Sierra de las Nieves” (Andalusia, Spain) has been carried out. It is a very environmentally diverse area, with numerous and contrasting lithological types, mediterranean macro-bioclimate and 4 thermotypes, from thermo-mediterranean (150 m) to oro-mediterranean (1919 m). The park is included in three very different biogeographical sectors (Rondeño: dolomites/limestones, Bermejense: peridotites, Aljibico: siliceous substrates) belonging to the Western Mediterranean subregion and main refuge of Abies pinsapo among other endemic and relict species. The study was carried out using the updated phytosociological method, with inventories taken mainly during the years 2017-2023 and complemented with previous data (1996-1998).
Keywords: Recursos naturales - Conservación; Biogeografía; Parque Nacional Sierra de las Nieves (Málaga) - Flora; Catalogue; Conservation; Natura 2000; Plant communities; Protected area; Sectorization; Relict; Biogeographical distribution